2014
DOI: 10.1186/1471-2164-15-1166
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of Rcr1 and analyses of its effect on transcriptome patterns during infection by Plasmodiophora brassicae

Abstract: BackgroundThe protist Plasmodiophora brassicae is a biotrophic soil-borne pathogen that causes clubroot on Brassica crops worldwide. Clubroot disease is a serious threat to the 8 M ha of canola (Brassica napus) grown annually in western Canada. While host resistance is the key to clubroot management, sources of resistance are limited.ResultsTo identify new sources of clubroot resistance (CR), we fine mapped a CR gene (Rcr1) from B. rapa ssp. chinensis to the region between 24.26 Mb and 24.50 Mb on the linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(181 citation statements)
references
References 87 publications
4
170
0
Order By: Relevance
“…Compared with the maternal parent, up‐regulated Bra019369 in the Brassica hexaploid encodes a SAUR (small auxin‐up RNA) protein (Chu et al., ), and this protein is tightly tied to auxin biosynthesis and the signaling pathway (Wu, Ma, Chen, Wang, & Wang, ; Wu, Liu et al., ; Wu, Okada et al., ). Up‐regulated TCONS_00018406, as a Bra019369 regulator, possibly take part in auxin‐dependent metabolism, thereby regulating plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the maternal parent, up‐regulated Bra019369 in the Brassica hexaploid encodes a SAUR (small auxin‐up RNA) protein (Chu et al., ), and this protein is tightly tied to auxin biosynthesis and the signaling pathway (Wu, Ma, Chen, Wang, & Wang, ; Wu, Liu et al., ; Wu, Okada et al., ). Up‐regulated TCONS_00018406, as a Bra019369 regulator, possibly take part in auxin‐dependent metabolism, thereby regulating plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…AT1G05530, its orthologous genes, involved in IAA metabolic pathway, plays a vital role in IAA homeostasis (Tanaka et al, 2014), and TCONS_00009958, targeting Bra031483, could be involved in the protein (Chu et al, 2014), and this protein is tightly tied to auxin biosynthesis and the signaling pathway (Wu, Ma, Chen, Wang, & Wang, 2012;Wu, Liu et al, 2012;Wu, Okada et al, 2012 LncRNAs can function as a member of the miRNA regulation network to realize the regulation of gene expression (Wu, Wang, Wang, & Wang, 2013). For example, the interaction between miR-NAs and lncRNAs is an important mechanism to maintain phosphate homeostasis.…”
Section: Regulation Of Lncrnas Might Increase the Possibility For Amentioning
confidence: 99%
“…To date, studies of the molecular basis of clubroot resistance from Brassica crops mainly focused on qualitative resistance, especially in Chinese cabbage (Chen et al, 2016) and canola (Chu et al, 2014). However, illuminating molecular mechanism of quantitative resistance could lead to insight into the relationship between qualitative and quantitative resistance, thus to guild utilization of the two types to produce durably resistant cultivar (Jubault et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, previous studies have focused on understanding the mechanisms underlying clubroot disease resistance in Brassica species, including Brassica rapa and Brassica napus . Chu et al (2014) identified differentially expressed genes (DEGs) involved in the signaling metabolism of jasmonate and ethylene, defensive deposition of callose and the biosynthesis of indole-containing compounds, which were all significantly up-regulated in clubroot-resistant plants compared with susceptible cultivars. More recently, Chen et al (2016) confirmed that genes associated with PAMPs, calcium ion influx, hormone signaling, PR, transcription factors, and cell-wall modification played important roles in host– P. brassicae interactions during the early stages of infection by P. brassicae , based on transcriptome analysis of B. rapa .…”
Section: Introductionmentioning
confidence: 99%
“…The former encodes a TIR-NB-LRR and was functionally confirmed. With the development of genomic and molecular genetics, several loci were further identified using newly developed marker techniques 147 . Yu et al 148 applied BSA-seq and identified a novel resistance gene, Rcr1, and two candidates encoding TIR-NB-LRRs.…”
Section: Clubrootmentioning
confidence: 99%